A method for preparing porous carbon lithium iron phosphate positive electrode material using metal organic framework

By using metal organic frames as templates and raw materials, porous carbon lithium iron phosphate positive electrode material is prepared, which solves the problem of easy shedding of the coating products in the prior art, achieves higher conductivity and electrochemical properties, and promotes lithium iron phosphate The commercialization and industrialization of materials.

CN115172704BActive Publication Date: 2025-02-18JIANGSU UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210857173.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-20
Publication Date
2025-02-18
Estimated Expiration
2042-07-20

AI Technical Summary

Technical Problem

The existing lithium iron phosphate positive electrode material is prone to fall off during high temperature calcination, which affects the integrity and conductivity of the coating and limits its commercialization and industrialization development.

Method used

Using metal organic frames (such as MIL-68(Fe) or MIL-53(Fe)) as templates, by preparing porous lithium iron phosphate positive electrode materials, using metal organic frames as templates and raw materials, embedded in porous continuous carbon mesh to form Three-dimensional porous structure enhances the binding force between the coating agent and lithium iron phosphate and improves electrical conductivity.

Benefits of technology

It significantly improves the conductivity and electrochemical properties of lithium iron phosphate materials, enhances the integrity of coating, and improves the circulation performance and thermal stability of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115172704B_ABST
    Figure CN115172704B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing lithium iron phosphate material by using metal organic framework, belonging to the technical field of lithium ion battery materials, and the steps include: (1) preparing metal organic framework; (2) dispersing the prepared metal organic framework powder into ethanol solution, and dispersing LiH2PO4 powder into ethanol at the same time. Then, the LiH2PO4 solution is added dropwise into the above suspension under continuous stirring; (3) after the mixed precursor reactants are stirred at room temperature for 24 hours, the ethanol solution is evaporated at a water bath temperature of 80°C. The dried solid powder is transferred to a tubular furnace, and calcined under a reducing atmosphere to obtain a lithium iron phosphate carbon composite material. The preparation method provided by the present invention can obtain a lithium iron phosphate positive electrode material, and the rate performance and electrochemical performance of the lithium iron phosphate positive electrode material are improved after being applied to a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a method for preparing a porous carbon lithium iron phosphate positive electrode material by utilizing a metal organic framework. Background Art

[0002] Lithium iron phosphate is a new type of positive electrode material for lithium-ion batteries. As a positive electrode material for lithium-ion batteries, it has the advantages of low price, non-toxicity, good environmental compatibility, and good safety performance. It has been widely studied in recent years. However, its disadvantages such as low energy density, poor kinetic performance and lithium ion diffusion capacity limit the commercialization and industrialization development and progress of lithium iron phosphate. Therefore, it is of great practical significance to develop lithium iron phosphate positive electrode materials with high reversible discharge capacity, excellent cycle performance and high thermal stability.

[0003] At present, among the many preparation methods and electrochemical performance modifications of lithium iron phosphate, carbon coating, doping, etc. have improved the performance of lithium iron phosphate to a certain extent. However, in the existing technology for modified coating of lithium iron phosphate, the coated product is easy to fall off during high-temperature calcination, which further affects the integrity of the coating and reduces the conductivity.

[0004] Therefore, the market urgently needs a preparation method that can improve the bonding force between the coating agent and lithium iron phosphate and increase the conductivity of the lithium iron phosphate material to solve the above problems.

[0005] The above information disclosed in this Background section is only for enhancement of understanding of the background of the present disclosure and therefore it may contain information that does not constitute the prior art that is already known to one of ordinary skill in the art. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a lithium iron phosphate positive electrode material using a metal organic framework in view of the above-mentioned defects of the lithium iron phosphate positive electrode material in the prior art.

[0007] In order to achieve the above object, the present invention provides the following technical solution: a method for preparing a porous carbon lithium iron phosphate positive electrode material using a metal organic framework, characterized in that it comprises the following steps:

[0008] Step 1. Preparation of metal organic framework powder.

[0009] Step 2. Disperse the prepared metal organic framework powder into an ethanol solution, and at the same time disperse the LiH2PO4 powder into ethanol to form a suspension, and then add the LiH2PO4 solution dropwise into the above suspension under continuous stirring to obtain a mixed precursor reactant.

[0010] Step 3. Stir the mixed precursor reactants at room temperature for 24 hours, evaporate the ethanol solution at 80°C in a water bath to obtain a dried solid powder, transfer the dried solid powder to a tubular furnace, and calcine under a reducing atmosphere to obtain a lithium iron phosphate carbon composite material.

[0011] Preferably, the metal frame is MIL-68(Fe) or MIL-53(Fe).

[0012] Preferably, the preparation method of the metal frame MIL-68 (Fe) is to add FeCl3.6H2O and terephthalic acid to nn-dimethylformamide, perform ultrasonic dispersion, then add HF and HCl and stir until the raw materials are completely dissolved, and then transfer the dissolved solution to the first reactor, store it at 100°C for 5 days, and after natural cooling, wash and centrifuge it with n,n-dimethylformamide and acetone, and vacuum dry it at 100°C for 24 hours to obtain a light orange powder MIL-68 (Fe).

[0013] Preferably, the molar ratio of FeCl3.6H2O to terephthalic acid is 1:2.

[0014] Preferably, the preparation method of the metal frame MIL-53 (Fe) is as follows: ferric chloride hexahydrate, terephthalic acid and N, N-dimethylformamide are mixed, stirred and ultrasonically vibrated according to a set ratio to obtain a reaction liquid, the reaction liquid is poured into a polytetrafluoroethylene reactor, the reactor is placed in a constant temperature oven, and the reaction is carried out at 150° C. for 15 hours. After the reaction is completed, the reactor is taken out and cooled to room temperature to obtain a sample, the obtained sample is washed with deionized water, filtered with an air pump, and then soaked in ethanol for 24 hours, and finally vacuum dried in an air atmosphere at 150° C. for 24 hours.

[0015] Preferably, in the synthesis step of the metal framework MIL-53(Fe), the molar ratio of ferric chloride hexahydrate, terephthalic acid and N,N-dimethylformamide is 1:1:280.

[0016] Preferably, in step 2, the molar ratio of Fe atoms to Li atoms is controlled to be 1:(1-3).

[0017] Preferably, in step three, the reducing atmosphere is one or more of hydrogen and argon.

[0018] Preferably, the specific steps of calcination are: in the first stage, the temperature is raised to 350 degrees at a rate of 2°C / min and kept warm for 3 hours; in the second stage, the temperature is raised to 600 to 750°C at a rate of 5°C / min and then baked for 5 hours, and the lithium iron phosphate carbon composite material is obtained by cooling.

[0019] In the above technical solution, the technical effects and advantages provided by the present invention are:

[0020] 1. Use metal organic framework as template and raw material to prepare lithium iron phosphate material, embed lithium iron phosphate particles into porous continuous carbon network, prepare lithium iron phosphate material with three-dimensional porous structure, and effectively increase the migration speed of Li+ between the main body and interface of lithium iron phosphate material;

[0021] 2. The particles obtained by the present invention are uniform, have high capacitance, are small and uniform, and have obvious improvements in electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.

[0023] Figure 1 This is the XRD pattern of the metal frame MIL-53 (Fe) material;

[0024] Figure 2 This is the SEM image of the metal frame MIL-53 (Fe) material;

[0025] Figure 3 This is a SEM image of lithium iron phosphate carbon composite material;

[0026] Figure 4 The figure shows the charge and discharge at different rates. DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] In addition, the described features, structures or characteristics may be combined in one or more example embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the example embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, components, steps, etc. may be adopted. In other cases, well-known structures, methods, implementations or operations are not shown or described in detail to avoid obscuring various aspects of the present disclosure.

[0029] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0030] Embodiment 1:

[0031] like Figure 1-4 A method for preparing a porous carbon lithium iron phosphate positive electrode material using a metal organic framework is shown, comprising the following steps:

[0032] Step 1. Preparation of metal organic framework powder.

[0033] Step 2. Disperse 3.1 g of the prepared metal organic framework powder into 50 ml of ethanol solution, and at the same time disperse 1.04 g of LiH2PO4 powder into ethanol to form a suspension. Then, add the LiH2PO4 solution dropwise into the above suspension under continuous stirring to obtain a mixed precursor reactant.

[0034] Step 3. Stir the mixed precursor reactants at room temperature for 24 hours, evaporate the ethanol solution at 80°C in a water bath to obtain a dried solid powder, transfer the dried solid powder to a tubular furnace, and calcine under a reducing atmosphere to obtain a lithium iron phosphate carbon composite material.

[0035] Preferably, the metal frame is MIL-68(Fe).

[0036] Preferably, the preparation method of the metal frame MIL-68 (Fe) is to add FeCl3.6H2O and terephthalic acid to nn-dimethylformamide, perform ultrasonic dispersion, then add HF and HCl and stir until the raw materials are completely dissolved, and then transfer the dissolved solution to the first reactor, store it at 100°C for 5 days, and after natural cooling, wash and centrifuge it with n,n-dimethylformamide and acetone, and vacuum dry it at 100°C for 24 hours to obtain a light orange powder MIL-68 (Fe).

[0037] Preferably, in the synthesis step of the metal framework MIL-68 (Fe), 1.2mmol FeCl3.6H2O and 2.4mmol terephthalic acid are weighed. The volume of nn-dimethylformamide is 12ml, the volume of hydrofluoric acid added is 120ul, the concentration is 5mol / L, and the volume of hydrochloric acid added is 120ul, the concentration is 1mol / L.

[0038] Preferably, in step three, the reducing atmosphere is preferably hydrogen and argon, wherein hydrogen accounts for 10% and argon accounts for 90%.

[0039] Preferably, the specific steps of calcination are: preferably in the first stage, the temperature is raised to 350 degrees at a rate of 2°C / min and kept warm for 3 hours; in the second stage, the temperature is raised to 600 to 750°C at a rate of 5°C / min and then baked for 5 hours, and the lithium iron phosphate carbon composite material is obtained by cooling.

[0040] Example 2

[0041] Step 1. Preparation of metal organic framework powder.

[0042] Step 2. Disperse 2.37 g of the prepared metal organic framework powder into 50 ml of ethanol solution, and at the same time disperse 1.04 g of LiH2PO4 powder into ethanol to form a suspension. Then, add the LiH2PO4 solution dropwise into the above suspension under continuous stirring to obtain a mixed precursor reactant.

[0043] Step 3. Stir the mixed precursor reactants at room temperature for 24 hours, evaporate the ethanol solution at 80°C in a water bath to obtain a dried solid powder, transfer the dried solid powder to a tubular furnace, and calcine under a reducing atmosphere to obtain a lithium iron phosphate carbon composite material.

[0044] Preferably, the metal frame is MIL-53(Fe).

[0045] Preferably, the preparation method of the metal frame MIL-53 (Fe) is as follows: ferric chloride hexahydrate, terephthalic acid and N, N-dimethylformamide are mixed, stirred and ultrasonically vibrated according to a set ratio to obtain a reaction liquid, the reaction liquid is poured into a polytetrafluoroethylene reactor, the reactor is placed in a constant temperature oven, and the reaction is carried out at 150° C. for 15 hours. After the reaction is completed, the reactor is taken out and cooled to room temperature to obtain a sample, the obtained sample is washed with deionized water, filtered with an air pump, and then soaked in ethanol for 24 hours, and finally vacuum dried in an air atmosphere at 150° C. for 24 hours.

[0046] Preferably, in the synthesis step of the metal framework MIL-53(Fe), the molar ratio of ferric chloride hexahydrate, terephthalic acid and N,N-dimethylformamide is 1:1:280.

[0047] Preferably, in step three, the reducing atmosphere is preferably hydrogen and argon, wherein hydrogen accounts for 10% and argon accounts for 90%.

[0048] Preferably, the specific steps of calcination are: preferably in the first stage, the temperature is raised to 350 degrees at a rate of 2°C / min and kept warm for 3 hours; in the second stage, the temperature is raised to 600 to 750°C at a rate of 5°C / min and then baked for 5 hours, and the lithium iron phosphate carbon composite material is obtained by cooling.

[0049] Comparative Example 1

[0050] A method for preparing lithium iron phosphate material using a metal organic framework comprises the following steps:

[0051] Step 1: First, prepare the metal organic framework.

[0052] Step 2: Disperse 3.1 g of the prepared metal organic framework MIL-68 (Fe) powder into 50 ml of ethanol solution, and disperse 2.08 g of LiH2PO4 powder into 100 ml of ethanol. Then, add the LiH2PO4 solution dropwise into the above suspension under constant stirring.

[0053] Step 3: After the mixed precursor reactants are stirred at room temperature for 24 hours, the ethanol solution is evaporated in a water bath at 80° C. The dried solid powder is transferred to a tube furnace and calcined in a reducing atmosphere to obtain a lithium iron phosphate carbon composite material.

[0054] In the step 1, the metal frame MIL-68 (Fe) is preferred.

[0055] The preparation method of the metal frame MIL-68 (Fe) is as follows: FeCl3.6H2O and terephthalic acid are added to nn-dimethylformamide for ultrasonic dispersion, and then hydrofluoric acid and hydrochloric acid are added and stirred until the raw materials are completely dissolved, and then the solution is transferred to a first reaction kettle, stored at 100°C for 5 days, and after natural cooling, washed and centrifuged with n,n-dimethylformamide and acetone, and vacuum dried at 100°C for 24 hours to obtain a light orange powder MIL-68 (Fe).

[0056] In the synthesis step of the metal framework MIL-68 (Fe), 1.2 mmol FeCl3.6H2O and 2.4 mmol terephthalic acid were weighed. The volume of nn-dimethylformamide was 12 ml, the volume of hydrofluoric acid added was 120 ul, the concentration was 5 mol / L, and the volume of hydrochloric acid added was 120 ul, the concentration was 1 mol / L.

[0057] In the step three, the reducing atmosphere is preferably hydrogen and argon, wherein hydrogen accounts for 10% and argon accounts for 90%.

[0058] The specific steps of calcination are: preferably in the first stage, the temperature is raised to 350 degrees at a rate of 2°C / min and kept warm for 3 hours; in the second stage, the temperature is raised to 600 to 750°C at a rate of 5°C / min and then calcined for 5 hours, and the lithium iron phosphate carbon composite material is obtained by cooling.

[0059] Comparative Example 2

[0060] A method for preparing lithium iron phosphate material using a metal organic framework comprises the following steps:

[0061] Step 1: First, prepare the metal organic framework.

[0062] Step 2: Disperse 3.1 g of the prepared metal organic framework MIL-68 (Fe) powder into 50 ml of ethanol solution, and disperse 3.12 g of LiH2PO4 powder into 150 ml of ethanol. Then, add the LiH2PO4 solution dropwise into the above suspension under constant stirring.

[0063] Step 3: After the mixed precursor reactants are stirred at room temperature for 24 hours, the ethanol solution is evaporated in a water bath at 80° C. The dried solid powder is transferred to a tube furnace and calcined in a reducing atmosphere to obtain a lithium iron phosphate carbon composite material.

[0064] In the step 1, the metal frame MIL-68 (Fe) is preferred.

[0065] The preparation method of the metal frame MIL-68 (Fe) is as follows: FeCl3.6H2O and terephthalic acid are added to nn-dimethylformamide for ultrasonic dispersion, and then hydrofluoric acid and hydrochloric acid are added and stirred until the raw materials are completely dissolved, and then the solution is transferred to a first reaction kettle, stored at 100°C for 5 days, and after natural cooling, washed and centrifuged with n,n-dimethylformamide and acetone, and vacuum dried at 100°C for 24 hours to obtain a light orange powder MIL-68 (Fe).

[0066] In the synthesis step of the metal framework MIL-68 (Fe), 1.2 mmol FeCl3.6H2O and 2.4 mmol terephthalic acid were weighed. The volume of nn-dimethylformamide was 12 ml, the volume of hydrofluoric acid added was 120 ul, the concentration was 5 mol / L, and the volume of hydrochloric acid added was 120 ul, the concentration was 1 mol / L.

[0067] In the step three, the reducing atmosphere is preferably hydrogen and argon, wherein hydrogen accounts for 10% and argon accounts for 90%.

[0068] The specific steps of calcination are: preferably in the first stage, the temperature is raised to 350 degrees at a rate of 2°C / min and kept warm for 3 hours; in the second stage, the temperature is raised to 600 to 750°C at a rate of 5°C / min and then calcined for 5 hours, and the lithium iron phosphate carbon composite material is obtained by cooling.

[0069] Comparative Example 3

[0070] A method for preparing lithium iron phosphate material using a metal organic framework comprises the following steps:

[0071] Step 1: First, prepare the metal organic framework.

[0072] Step 2: Disperse 2.37 g of the prepared metal organic framework MIL-53 (Fe) powder into 50 ml of ethanol solution, and disperse 2.08 g of Li H2PO4 powder into ethanol. Then, add the Li H2PO4 solution dropwise into the above suspension under constant stirring.

[0073] Step 3: After the mixed precursor reactants are stirred at room temperature for 24 hours, the ethanol solution is evaporated in a water bath at 80° C. The dried solid powder is transferred to a tube furnace and calcined in a reducing atmosphere to obtain a lithium iron phosphate carbon composite material.

[0074] In the step 1, the metal frame MIL-53 (Fe) is preferred.

[0075] The preparation method of the metal frame MIL-53 (Fe) is as follows: after ferric chloride hexahydrate, terephthalic acid and N, N-dimethylformamide are mixed, stirred and ultrasonically vibrated in a certain proportion, the reaction solution is poured into a polytetrafluoroethylene reactor. The reactor is placed in a constant temperature oven and reacted for 15 hours at 150°C. After the reaction is completed, the reactor is taken out and cooled to room temperature. The obtained sample is washed with deionized water, filtered with an air pump, and then soaked in ethanol for 24 hours. Finally, vacuum dried for 24 hours in an air atmosphere at 150°C.

[0076] In the synthesis step of the metal framework MIL-53(Fe), the molar ratio of ferric chloride hexahydrate, terephthalic acid and N,N-dimethylformamide is 1:1:280.

[0077] In the step three, the reducing atmosphere is preferably hydrogen and argon, wherein hydrogen accounts for 10% and argon accounts for 90%.

[0078] The specific steps of calcination are: preferably, in the first stage, the temperature is raised to 350 degrees at a rate of 2°C / min and kept warm for 3 hours; in the second stage, the temperature is raised to 600 to 750°C at a rate of 5°C / min and then calcined for 5 hours, and cooled to obtain the lithium iron phosphate carbon composite material.

[0079] Comparative Example 4

[0080] A method for preparing lithium iron phosphate material using a metal organic framework comprises the following steps:

[0081] Step 1: First, prepare the metal organic framework.

[0082] Step 2: Disperse 2.37 g of the prepared metal organic framework MIL-53 (Fe) powder into 50 ml of ethanol solution, and disperse 3.12 g of Li H2PO4 powder into ethanol. Then, add the Li H2PO4 solution dropwise into the above suspension under constant stirring.

[0083] Step 3: After the mixed precursor reactants are stirred at room temperature for 24 hours, the ethanol solution is evaporated in a water bath at 80° C. The dried solid powder is transferred to a tube furnace and calcined in a reducing atmosphere to obtain a lithium iron phosphate carbon composite material.

[0084] In the step 1, the metal frame MIL-53 (Fe) is preferred.

[0085] The preparation method of the metal frame MIL-53 (Fe) is as follows: after ferric chloride hexahydrate, terephthalic acid and N, N-dimethylformamide are mixed, stirred and ultrasonically vibrated in a certain proportion, the reaction solution is poured into a polytetrafluoroethylene reactor. The reactor is placed in a constant temperature oven and reacted for 15 hours at 150°C. After the reaction is completed, the reactor is taken out and cooled to room temperature. The obtained sample is washed with deionized water, filtered with an air pump, and then soaked in ethanol for 24 hours. Finally, vacuum dried for 24 hours in an air atmosphere at 150°C.

[0086] In the synthesis step of the metal framework MIL-53(Fe), the molar ratio of ferric chloride hexahydrate, terephthalic acid and N,N-dimethylformamide is 1:1:280.

[0087] In the step three, the reducing atmosphere is preferably hydrogen and argon, wherein hydrogen accounts for 10% and argon accounts for 90%.

[0088] The specific steps of calcination are: preferably, in the first stage, the temperature is raised to 350 degrees at a rate of 2°C / min and kept warm for 3 hours; in the second stage, the temperature is raised to 600 to 750°C at a rate of 5°C / min and then calcined for 5 hours, and cooled to obtain the lithium iron phosphate carbon composite material.

[0089] The samples prepared in the embodiment and the comparative example were respectively used as positive electrode materials for lithium-ion batteries to prepare positive electrode sheets. The specific process is as follows:

[0090] (1) The prepared powdered positive electrode material was mixed with acetylene black (conductive agent) and polyvinylidene fluoride (PVDF, binder) at a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added as a dispersant, and ground into a slurry; then, the slurry was evenly coated on an aluminum foil, vacuum dried at 120° C. for 12 h, and transferred to an argon atmosphere glove box for standby use;

[0091] (2) A half-cell was assembled in an argon atmosphere glove box, with metallic lithium as the counter electrode and LiPF6 / ethylene carbonate (EC:DMC:DEC=1:1:1 by volume) as the electrolyte. A button cell of the assembled specification was CR2016, and constant current charge and discharge mode was used for charge and discharge.

[0092] Table 1 shows the discharge capacity retention rate and rate performance test results of the button-type battery prepared in the embodiment of the present invention after 100 cycles.

[0093]

[0094] Although the technical solutions of the present invention have been described and listed in detail, it should be understood that it is obvious to those skilled in the art to make modifications to the above embodiments or adopt equivalent alternatives. These modifications or improvements made without departing from the spirit of the present invention are within the scope of protection required by the present invention.

Claims

1. A method for preparing a porous carbon lithium iron phosphate positive electrode material using a metal organic framework, characterized in that: The following steps are involved: Step 1. Preparation of metal organic framework powder; Step 2. Dispersing the prepared metal organic framework powder into an ethanol solution, and dispersing the LiH2PO4 powder into ethanol to form a suspension, and then adding the LiH2PO4 solution dropwise into the suspension under constant stirring to obtain a mixed precursor reactant; Step 3. After the mixed precursor reactants are stirred at room temperature for 24 hours, the ethanol solution is evaporated at a water bath temperature of 80°C to obtain a dried solid powder, and the dried solid powder is transferred to a tubular furnace and calcined under a reducing atmosphere to obtain a lithium iron phosphate carbon composite material; The metal organic framework is MIL-68(Fe) or MIL-53(Fe); The preparation method of the metal frame MIL-68 (Fe) is as follows: FeCl3.6H2O and terephthalic acid are added to n-dimethylformamide, ultrasonically dispersed, and then HF and HCl are added and stirred until the raw materials are completely dissolved, and then the dissolved solution is transferred to a first reaction kettle, stored at 100° C. for 5 days, and after natural cooling, washed and centrifuged with n,n-dimethylformamide and acetone, and vacuum dried at 100° C. for 24 hours to obtain light orange powder MIL-68 (Fe); The preparation method of the metal frame MIL-53 (Fe) is as follows: ferric chloride hexahydrate, terephthalic acid and N, N-dimethylformamide are mixed, stirred and ultrasonically vibrated according to a set ratio to obtain a reaction liquid, the reaction liquid is poured into a polytetrafluoroethylene reactor, the reactor is placed in a constant temperature oven, and the reaction is carried out at 150° C. for 15 hours. After the reaction is completed, the reactor is taken out and cooled to room temperature to obtain a sample, the obtained sample is washed with deionized water, filtered with an air pump, and then immersed in ethanol for 24 hours, and finally vacuum dried for 24 hours in an air atmosphere at 150° C.

2. The method for preparing a porous carbon lithium iron phosphate positive electrode material using a metal organic framework according to claim 1, characterized in that: The molar ratio of the FeCl3.6H2O to terephthalic acid is 1:

2.

3. The method for preparing a porous carbon lithium iron phosphate positive electrode material using a metal organic framework according to claim 1, characterized in that: In the synthesis step of the metal framework MIL-53(Fe), the molar ratio of ferric chloride hexahydrate, terephthalic acid and N,N-dimethylformamide is 1:1:

280.

4. The method for preparing a porous carbon lithium iron phosphate positive electrode material using a metal organic framework according to claim 1, characterized in that: In step 2, the molar ratio of Fe atoms to Li atoms is controlled to be 1:(1-3).

5. The method for preparing a porous carbon lithium iron phosphate positive electrode material using a metal organic framework according to claim 1, characterized in that: In step three, the reducing atmosphere is one or more of hydrogen and argon.

6. The method for preparing a porous carbon lithium iron phosphate positive electrode material using a metal organic framework according to claim 1, characterized in that: The specific steps of calcination are: in the first stage, the temperature is raised to 350 degrees at a rate of 2°C / min and kept warm for 3 hours; in the second stage, the temperature is raised to 600 to 750°C at a rate of 5°C / min and then calcined for 5 hours, and the lithium iron phosphate carbon composite material is obtained by cooling.

Citation Information

Patent Citations

  • Preparation method of positive electrode material for lithium sulfur battery

    CN109461906A

  • Silicon-oxygen-carbon microsphere composite cathode material and preparation method and application thereof

    CN110048101A